Interactive Games, E-books, and Methods to Support Arabic Language Learning Upper Secondary School State Islamic Institute - Gonzalez Armando; Sergeev Robert; Gluubb Ramachandran (Lingeduca: Journal of Language and Education Studies, 2023)
Arabic lessons taught by teachers in class use various teaching media that are designed to be as attractive as possible. One of these media is an interactive game and e-book and then the teaching method that will be used by researchers in learning using this media is the direct learning method. The purpose of this study was to find out how important interactive game media, e-books and methods that support learning Arabic for MTsM students in Solok City. The research method used in this study is the quantitative method, the researcher will examine how important the media and teaching methods are. The results of the study prove that interactive game media, e-books and the methods used can affect students' enthusiasm and understanding of the material being taught. In this study it can be seen that the use of interactive games, e-books with direct learning methods can influence students' enthusiasm and understanding of the material being taught and can be applied to other lessons.